John Calvin and the Reformed tradition on the jurisdiction of the church - Coertzen, Pieter 1943- (2001)
John Calvin’s view on the power of jurisdiction in the church, as he writes about it in the Institutes, is expounded in this article. Firstly, attention is given to the spiritual authority of the church, followed by an exposition of the power of the church to exercise jurisdiction. Lastly the current situation in Reformed circles on the jurisdiction of the church is discussed.
Keywords: Spiritual Authority; Reformed Theology; Jurisdiction Of The Church; Church Polity And Church Government